Towards an understanding of the structure, function and cause of gang formation in Cape Town - Pinnock, Don (Department of Public Law, 2023)
One of the more speculative tasks of this book is to assess what impact those gangs are likely to have on the changes urban South Africa will undergo in the last two decades of the 20th Century, be it peaceful, reactionary or revolutionary. A rather more immediate task, and a necessary precursor, is to explore the functions of these gangs and the causes of their existence. But this immediately leads us into wider and deeper areas, to poverty, social dislocation and strategies of class defence. And within and beyond these conditions can be found an ongoing struggle for survival, a class struggle, and the outline of the state itself. (It is here that one encounters a strange paradox: a system which upholds law and order while at the same time creating the preconditions for its breakdown.) But we must start with the street gangs. A count in 30 areas on the Cape Flats during 1982 found in daily existence 280 groups who identified themselves as gangs. Nearly 80 per cent of the gang members interviewed for this study said their group was more than 100 strong, 54 per cent put the figure at 200 and several as high as 2000. An extremely rough estimate gives a figure of 50,000 youths who would define themselves as gang members, or about five per cent of the city's total population.